KAITAN PERSEPSI GANGGUAN MENTAL DENGAN STRES AKADEMIK PADA SISWA SEKOLAH MENENGAH PERTAMA - Hastuti, Rahmah; Wahyono, Dhamodhara; Caroline, Gabriella Dinna (Jurnal Psimawa : Diskursus Ilmu Psikologi dan Pendidikan, 2025)
This study investigated the link between the perception of mental disorders and academic stress in 206 Jakarta junior high school students, aged 11–15. Employing a quantitative correlational method, the research found a significant positive relationship between the two variables (rs = 0.543, p < 0.05). Perceptions related to depression, anxiety, and academic pressures like workload and time constraints were all positively correlated with academic stress. Interestingly, female students demonstrated a higher perception of mental disorders than males, though academic stress levels did not differ significantly by gender. However, no significant difference was found in academic stress levels between males and females. These findings underscore the need for targeted interventions. They provide a valuable foundation for mental health practitioners, educators, and parents to develop strategies that mitigate the negative impact of these perceptions on student well-being, thereby supporting adolescent mental health and overall quality of life.